Comparative Analysis of Organizational Performance Across Institutional Sectors Based on Performance Technology Implementation - Neni Sutrisni; Brigita Moudy Puspa Wardani; Dian Rizky Arfiana (Perkumpulan Pengelola Jurnal (PPJ) PAUD Indonesia, 2026)
This study presents a comparative analysis of the implementation of performance technology across various sectors, driven by the increasing adoption of digital technology but not yet accompanied by equitable performance outcomes. This study aims to examine differences in organizational performance across sectors and identify best practices that contribute to improved performance. The method used is a comparative quantitative approach with a cross-sectional design, involving samples from the education, industry, government, and public services sectors through a stratified random sampling technique. Data collection was conducted using a Likert-scale questionnaire that has been tested for validity and reliability, while data analysis used ANOVA and Tukey's post hoc test to identify significant differences between groups. The results show significant differences in performance across sectors, with the industry sector as the most superior, followed by public services, education, and government. These findings confirm that the success of performance technology implementation is influenced by organizational readiness, human resource competency, and the integration of technology systems with work processes. The conclusions of this study emphasize the importance of a contextual approach in the implementation of performance technology and the need for capacity building and adaptive strategies in each sector. Further research is recommended to examine moderating factors in more depth with a longitudinal design to gain a more comprehensive understanding.